Resolving Bank Failures and Institutions : Is there a Link? Some Empirical Evidence - Rawlins, Marlon; Zanforlin, Luisa (Washington, D.C. : International Monetary Fund, 2021)
Policymakers across countries have been seeking to strengthen the institutional framework to control fiscal costs and feedback effects to the real economy generated by bank failures. On a cross-section of countries, we find evidence that suggests that bank supervisors' intervention in bank failures may be positively associated with some aspects of the administrative and regulatory framework. Our results appear to hold also during times of financial instability. Finally, we find some evidence that the same institutional features may be associated with lower fiscal outlays during banking crises.
Off-Campus Access: No User ID or Password Required
On-Campus Access: No User ID or Password Required
Mode of access: Internet
Keywords: Banks; Depository Institutions; Financial Institutions and Services; Micro Finance Institutions; Mortgages